THE ROLE AND IMPACT OF KOSOVO LIBERATION ARMY IN INTERNATIONAL DIPLOMACY: A CASE STUDY OF ISSUES OF KOSOVO FROM 1998 TO 1999 - Reshat Nurboja (European Scientific Journal, ESJ, 2014)
The paper in itself involves International insistence in all aspects in solving Kosovo issue within the framework of Yugoslavia-Serbia and the various attempts of Albanian people, who do not allow something like this to happen at all. In the beginning, politic alternative of Kosovo attempted for years in achieving its political rights with politic means, peaceful policy, known as political Doctrine of Ibrahim Rugova, and Democratic League of Kosovo respectively, which by time as estimated by all, was accepted that with such, policy may be able to achieve what the people of Kosovo was determined in achieving for centuries. In this paper, I documented that the Kosovo case was completely ignored in International Conference during the entire period before the presentation of KLA (Liberation Army of Kosovo). After the signing of Agreement of Dayton in 1995, the situation in Kosovo became worsened. Kosovan Albanians looked behind their shoulders and learnt that Bosnians, Croatians, Slovenians, and Macedonians got separated from Yugoslavia and created independent countries, whereas Kosovan Leadership still continued with the call for endurance by proclaiming peaceful policy and still not understanding that International Diplomacy was compelled to evolve contrary with their historical determinations to preserve Yugoslavia by all means. Albanian people understood this idea on time and as a result, KLA came to surface an enabled International Diplomacy in general and American Diplomacy in particular to incorporate the solution of Kosovo issue within the mosaic of status solving, as it was done to other Republics in former Yugoslavia.